Gender and Exit Exams in Higher Education: A Systematic Literature Review - Teshome, Samson Worku (Early Publishing, 2025)
This study aims to systematically review existing literature on the relationship between gender and exit exams in higher education, identifying key trends, challenges, and gaps in current research. This systematic review explores the intersection of gender and exit exams in higher education, synthesizing findings from 20 studies published between 1994 and 2024. The review examines how gender influences students’ performance, perceptions, and outcomes related to exit exams, as well as the broader implications for equity and quality assurance in higher education. Using the PRISMA framework, a comprehensive search was conducted across academic databases, yielding 587 articles. After screening for relevance, 32 studies were included based on predefined inclusion criteria. Data extraction focused on authorship, objectives, methodologies, geographic contexts, and gender-specific issues. The results reveal significant disparities in how male and female students perceive and perform in exit exams, with women often reporting higher anxiety levels but demonstrating comparable or superior performance in certain disciplines. The narrative analysis highlights the role of sociocultural factors, institutional policies, and exam design in shaping these outcomes. This review underscores the need for gender-sensitive approaches to designing and implementing exit exams, ensuring equitable opportunities for all students.